Managing Director's Statement to the Development Committee. (Policy Papers; Policy Paper, 2006)
A Statement from the Managing Director of the International Monetary Fund, Rodrigo de Rato, for the Committee's seventy-third meeting to be held in Washington, D.C., on Sunday, April 23, 2006.